IDENTIFIKASI PENGARUH AKTIVITAS MATAHARI PADA FOF2 DI BIAK DAN TEC IONOSFER DI BANDUNG - Wilsom Sinambela; Anwar Santoso; - Asnawi (Lembaga Penerbangan dan Antariksa Nasional, 2004)
The identification of solar activity effets on ionospheric layer has been investigated based on data of monthly mean of critical frequency of ionospheric layer F2 (foF2) over Biak during the period 1991-1995, and data Total Electron Content (TEC) over Bandung during the period 1997-2000. Data of daily TEC over Bandung were used for identification of ionospheric storms due to large solar flares that occurred on September 23, 1998 and July 14, 2000 that followed by Coronal Mass Ejection (CME) event. From analysis it was found that solar activities such as sunspot and solar flare influences the ionospheric layer both short-term and long-term. By taking the moving average of 12 months and using linier regression analysis it was found that the variation of ionospheric foF2 and TEC following the variation of solar activity indices; the decreasing of solar activity during the descending phase of solar cycle-22 (1991-1995) is followed by the decreasing of ionospheric foF2 over Biak, with strong correlation coefficient of 0.96; the increasing of solar activity during the ascending phase of solar cycle-23 (1997-2000) is followed by the increasing of ionospheric TEC over Bandung, with strong correlation coefficient of 0.98. From identification of the large solar flares effects that occurred on September 23, 1998 and July 14, 2000 that followed by CME event causes the ionospheric storm about 2-days after solar flare. From identification also it seems that small solar flares no causes ionospheric storm in these period.